RNA-targeted therapies - Silencing rogue - Wood, M (2008)
Advances in RNA biology have led to the development of nucleic acid therapeutic agents targeting RNA. Such agents are small oligonucleotides of diverse structures and chemistries that resemble standard pharmacotherapeutics more than conventional gene therapies, with the ability to yield a range of therapeutic transformations on different types of target RNA. © 2008 The Biochemical Society.